2017
DOI: 10.1038/srep43056
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of denitrification vis-à-vis monsoon in the Arabian Sea since Late Miocene

Abstract: In the Arabian Sea, South Asian monsoon (SAM)-induced high surface water productivity coupled with poor ventilation of intermediate water results in strong denitrification within the oxygen minimum zone (OMZ). Despite the significance of denitrification in the Arabian Sea, we have no long-term record of its evolution spanning the past several million years. Here, we present the first record of denitrification evolution since Late Miocene (~10.2 Ma) in the Eastern Arabian Sea, where the SAM generates moderate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 39 publications
8
47
1
Order By: Relevance
“…The increase in δ 15 N (Figure d) in conjunction with increased abundance of diatoms, TOC, and the Ba/Al ratio suggests that denitrification is occurring in the water body in response to increased organic matter load (Narkis et al, ). Based on previous studies in the region (Altabet et al, ; Altabet et al, ; Gaye‐Haake et al, ; Tripathi et al, ) δ 15 N values above 6‰ have been ascribed to indicate sustained denitrification in the water column. In the Miocene record of Site 722, δ 15 N increases above 6‰ for the first time ~11 Ma.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The increase in δ 15 N (Figure d) in conjunction with increased abundance of diatoms, TOC, and the Ba/Al ratio suggests that denitrification is occurring in the water body in response to increased organic matter load (Narkis et al, ). Based on previous studies in the region (Altabet et al, ; Altabet et al, ; Gaye‐Haake et al, ; Tripathi et al, ) δ 15 N values above 6‰ have been ascribed to indicate sustained denitrification in the water column. In the Miocene record of Site 722, δ 15 N increases above 6‰ for the first time ~11 Ma.…”
Section: Discussionmentioning
confidence: 98%
“…This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. denitrification in the region and concluded that productivity did not significantly increase prior to 3.1 Ma during the Mid-Pliocene Warm Period (Tripathi et al, 2017). Tripathi et al (2017) thus assume that a weaker SAM must have persisted from at least~10.2 Ma onward.…”
Section: The Indian Ocean Oxygen Minimum Zonementioning
confidence: 95%
See 2 more Smart Citations
“…Despite the significance of denitrification in global climate change, no long-term record of its evolution in the Arabian Sea during the Miocene-Pliocene period existed till date; the longest record available goes back to 1 million years from the western Arabian Sea (Altabet et al, 1999). To fill this gap, Tripathi et al (2017) studied various denitrification (δ 15 N of sedimentary organic matter, SOM), provenance (δ 13 C of SOM, C/N ratio) and productivity (total organic carbon (TOC) and total nitrogen (TN)) proxies in sediment record of the IODP Site U1456, spanning the last 10 Myr (Fig. 3).…”
Section: Records Of Past Changes In Ocean-climate During the Neogenementioning
confidence: 99%